Digital design sketching using the tablet PC - Mark Evans; Noor N. Aldoy (2016)
As digital sketching continues to emerge as an alternative to paper-based techniques, a qualitative, triangulated longitudinal study of 9 months duration was undertaken to explore the capabilities of the tablet Personal Computer (PC) to support portable sketching during industrial/product design activity. The methodology involved the unrestricted use of tablet PCs by 16 final year undergraduate industrial/product design students for an entire academic year, with data collection through a sketching exercise (participant and expert questionnaires), design exercise (questionnaire), focus group (coding and clustering) and final questionnaire. The conclusions indicate that the tablet PC represents a significant development in the support of sketching capability by increasing confidence which can have a positive impact on the generation of design ideas.